Rational design of adhesives for effective underwater bonding - Li, Sidi; Ma, Chuao; Hou, Bin; Liu, Hongliang (Frontiers in Chemistry, 2022)
Underwater adhesives hold great promises in our daily life, biomedical fields and industrial engineering. Appropriate underwater bonding can reduce the huge cost from removing the target substance from water, and greatly lift working efficiency. However, different from bonding in air, underwater bonding is quite challenging. The existence of interfacial water prevents the intimate contact between the adhesives and the submerged surfaces, and water environment makes it difficult to achieve high cohesiveness. Even so, in recent years, various underwater adhesives with macroscopic adhesion abilities were emerged. These smart adhesives can ingeniously remove the interfacial water, and enhance cohesion by utilizing their special physicochemical properties or functional groups. In this mini review, we first give a detail introduction of the difficulties in underwater bonding. Further, we overview the recent strategies that are used to construct underwater adhesives, with the emphasis on how to overcome the difficulties of interfacial water and achieve high cohesiveness underwater. In addition, future perspectives of underwater adhesives from the view of practical applications are also discussed. We believe the review will provide inspirations for the discovery of new strategies to overcome the obstacles in underwater bonding, and therefore may contribute to designing effective underwater adhesives.